2021
DOI: 10.1016/j.amsu.2021.102448
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet indices as a biomarker for the diagnosis of acute appendicitis and as a predictor of complicated appendicitis: A meta-analysis

Abstract: Introduction Acute appendicitis is one of the most common surgical emergencies worldwide. Clinical scoring system systems have been developed to diagnose acute appendicitis, but insufficient to predict the complication. The amount of serum biomarkers elevates in response to acute inflammation, which could be beneficial for diagnostic tools. Accordingly, a meta-analysis was conducted to evaluate the efficacy of platelet indices, including mean platelet volume (MVP) and platelet distribution width (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…A high value of MPV can be found in chronic diseases while lower MPV values can be found in acute diseases, such as acute appendicitis. PDW is an indicator of variation in platelet size, which can be a sign of active platelet release [5,6,17,18]. PDW, RDW, and platelet values in patients diagnosed with uncomplicated appendicitis may be a guide in choosing patients to be treated with antibiotics only [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high value of MPV can be found in chronic diseases while lower MPV values can be found in acute diseases, such as acute appendicitis. PDW is an indicator of variation in platelet size, which can be a sign of active platelet release [5,6,17,18]. PDW, RDW, and platelet values in patients diagnosed with uncomplicated appendicitis may be a guide in choosing patients to be treated with antibiotics only [17].…”
Section: Introductionmentioning
confidence: 99%
“…PDW is an indicator of variation in platelet size, which can be a sign of active platelet release [5,6,17,18]. PDW, RDW, and platelet values in patients diagnosed with uncomplicated appendicitis may be a guide in choosing patients to be treated with antibiotics only [17].…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al performed a systematic review and meta-analysis on the correlation between AA and MPV and concluded that MPV was lower in patients with AA [ 8 ]. Tullavardhana et al looked at platelet indices in AA in a meta-analysis and suggested that lower MVP values could function as a marker of AA [ 32 ]. Shen et al concluded in their meta-analysis that only MPV, but no other platelet indices, vary in AA cases [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we presented higher NLR reflecting inflammatory response related to tacrolimus overdose, higher MPV may result from the aforementioned platelet-to-leucocytes interaction. According to the meta-analysis conducted by Tullavardana et al, mean platelet volume (MVP) was a potential biomarker for the diagnosis of acute states, including appendicitis [ 30 ]. Meyer et al, in their study, presented inflammatory cascade induction via NF-κB9 (nuclear factor kappa-light-chain-enhancer of activated B cells), signaling endothelial colony progenitor cells induced by tacrolimus [ 31 ].…”
Section: Discussionmentioning
confidence: 99%